Cranio-morphometric and aDNA corroboration of the Austronesian dispersal model in ancient Island Southeast Asia: Support from Gua Harimau, Indonesia - Matsumura, Hirofumi (PLoS One, 2018)
The Austronesian language is spread from Madagascar in the west, Island Southeast Asia (ISEA) in the east (e.g. the Philippines and Indonesian archipelagoes) and throughout the Pacific, as far east as Easter Island. While it seems clear that the remote ancestors of Austronesian speakers originated in Southern China, and migrated to Taiwan with the development of rice farming by c. 5500 BP and onto the northern Philippines by c. 4000 BP (the Austronesian Dispersal Hypothesis or ADH), we know very little about the origins and emergence of Austronesian speakers in the Indonesian Archipelago. Using a combination of cranial morphometric and ancient mtDNA analyses on a new dataset from Gua Hairmau, that spans the pre-Neolithic through to Metal Period (5712—5591cal BP to 1864—1719 cal BP), we rigorously test the validity of the ADH in ISEA. A morphometric analysis of 23 adult male crania, using 16 of Martin’s standard measurements, was carried out with results compared to an East and Southeast Asian dataset of 30 sample populations spanning the Late Pleistocene through to Metal Period, in addition to 39 modern samples from East and Southeast Asia, near Oceania and Australia. Further, 20 samples were analyzed for ancient mtDNA and assigned to identified haplogroups. We demonstrate that the archaeological human remains from Gua Harimau cave, Sumatra, Indonesia provide clear evidence for at least two (cranio-morphometrically defined) and perhaps even three (in the context of the ancient mtDNA results) distinct populations from two separate time periods. The results of these analyses provide substantive support for the ADH model in explaining the origins and population history of ISEA peoples.